Um olhar para as infâncias de uma escola municipal de ensino fundamental de Santa Maria - Silva, Sabrina Marafiga Cardoso da (2023)
This research is linked to the Professional Master's Course, of the Postgraduate Program in Public Policies and Educational Management, in the Pedagogical Management and Educational Contexts Research Line and addresses the theme: the childhood of children in situations of "social vulnerability" The objective general definition was defined: Understanding how the situation of vulnerability affects the childhood of children in their first years of schooling. As specific objectives, priority was given to identifying which characteristics mark the childhood of children in vulnerable communities, recognizing how play is constituted, the spaces of childhood (where they play in the community and at school), Knowing the dreams of children who attend the Municipal Elementary School of Santa Maria. The theoretical framework was based on studies by Áries (1981), Costa (2023), Freire (1968, 1993 ,1996), Kramer (2007), Kuhlmann (1998, 2001). The research with a qualitative approach, inspired by authors such as Faria; Demartini; Prado (2002), Corsaro (2005, 2007) and Müller; Carvalho (2009). The research was developed based on meetings with children from the first to the fourth year of elementary school at Escola Municipal de Ensino Fundamental São João Batista, located in a socially vulnerable community in Santa Maria/RS. Strategies for data production were used to propose drawings, listen to and observe children, as well as play itself. The data collected was analyzed according to Bardin (2011, 2015) through content analysis, which resulted in two topics: Dreaming, imagining and fantasizing... that's what being a child is! Dreaming about BEING/HAVING/KNOWING... idealizations of a better future, this is also being a child! The research demonstrates the perspective of the children themselves, their views, on how they live, feel and perceive the vulnerability in which they are inserted, collectively reflecting on the different ways in which children live their childhoods in these contexts. The technical/educational product is a proposal for a training meeting with the school's teachers, in which some materials produced by the children during the research will be exposed and delivered to the teachers with a view to collective reflection on teaching work with the children.